A New Vaccine Candidate Strain of Coxsackievirus B5 Selected on the Basis of its Biological Properties - Yuhan Liu; Zhaoyang Chu; Ming Zhang; Junwei Chen; Jiansheng liu; Changzeng Feng; Shaohui Ma (Zoonoses, 2025)
Evidence indicates that coxsackievirus B5 (CVB5) can cause meningitis, and hand, foot, and mouth disease (HFMD), and is associated with type 1 diabetes. No effective drug or vaccine is available for treating CVB5 infections or controlling outbreaks. The Vero-cell-adapted vaccine candidate strain KM299-L05 underwent comprehensive phylogenetic analysis, sequence alignment, assessment of virulence in BALB/c mice, Vero cell acclimation, three successive rounds of plaque purification, preparation of experimental vaccines, and immunogenicity evaluation. KM299-L05 was the most virulent strain in BALB/c mice. Its infectious titer reached 10 8.0 CCID 50 /mL in Vero cells, and it belonged to the Chinese epidemic genotype C3. An inactivated CVB5 vaccine derived from the KM299-L05 strain produced neutralizing antibodies with a titer range from 1:384 to 1:768 against a variety of clinical CVB5 isolates, particularly the prototype strain. Maternal antibodies fully protected all examined suckling BALB/c mice against lethal challenge. Although the study was limited to neonatal mice, our findings suggested that the KM299-L05 strain has potential as a novel CVB5 vaccine candidate in China, and provide a rationale for the development of a CVB5 vaccine.